Redox Potential, the Main Barrier of Laccase-Mediated Biobleaching of Pulp in Paper Industry - Parsia, Yasaman; Sorooshian, Shahryar (Trade Science Inc., 2016)
A recently published article identified the main difficulties of implementing laccases at industrial scale for eco-friendly biobleaching of pulps for papers. This paper analyses the difficulties, mathematically, to prioritize them. Expert’s opinion is input data for the analysis. Multi-criteria decision making method is used for analysis. From the result and among the barriers that effect on stability of laccase, Redox potential with 52.2% priority is the most important difficulties; it is followed by pH with 25.3% priority. Moreover, this paper also provides a list of suggestion for future studies.